Hubungan Content Marketing Affilate dan Online Review Platform E-Commerce Shopee Terhadap Keputusan Pembelian Mahasiswa Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan - Paramithasari, Indri; Mubarrok, Solahuddin (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to measure the influence of affiliate content marketing and online reviews on the Shopee platform on purchasing decisions of Islamic economics students at STAI Syaichona Moh. Cholil Bangkalan. This study uses a quantitative approach and uses Islamic economics students at STAI Syaichona Moh. Cholil Bangkalan as the object of research. The number of samples used in this study was 66 respondents. Data collection techniques using questionnaires and data processing and hypothesis testing using IBM SPSS Statistics 25. In this study, the X1 variable obtained a t-count result of 81.203> t table which has a value of 1,670 obtaining a significance value of 0.000 <0.05, it can be concluded that the content marketing affiliate variable partially has a significant effect on purchasing decisions, and the X2 variable obtained a t-count result of 78.945> from the t table which has a value of 1,670 obtaining a significance value of 0.000 <0.05, it can be concluded that the online review variable partially has a significant effect on purchasing decisions, while simultaneously content marketing affiliates and online reviews both have a significant effect as evidenced by the results of the f-count value of 14.780> f table 3.14 producing a significance value <0.05 which is 0.000. The R square value of 0.319 means that the variables of content marketing affiliate and online customer review contribute significantly together or simultaneously to the purchasing decision variable of 31.9% and the remaining 68.1% is influenced by other variables outside this study. Due to time constraints, the researcher only took the object of research on the 2020 batch of Islamic economics students at STAI Syaichona Moh. Cholil Bangkalan, and only on users of the Shopee platform application. This can be used as a suggestion for further researchers. The novelty in this study combines the variables of content marketing affiliate and online review on purchasing decisions made by the 2020 batch of Islamic economics students at STAI Syaichona Moh. Cholil Bangkalan who are users of the Shopee platform application.